If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(t + -87) = 10 Reorder the terms: 5(-87 + t) = 10 (-87 * 5 + t * 5) = 10 (-435 + 5t) = 10 Solving -435 + 5t = 10 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '435' to each side of the equation. -435 + 435 + 5t = 10 + 435 Combine like terms: -435 + 435 = 0 0 + 5t = 10 + 435 5t = 10 + 435 Combine like terms: 10 + 435 = 445 5t = 445 Divide each side by '5'. t = 89 Simplifying t = 89
| -5(c-89)=-30 | | 13.7b-3=3.43b | | 74-2x=89-3x | | 13.7b-3=3-43b | | 48=12xn | | 19=5a-6 | | -189=-2x-3(7x+17) | | 81-x=94-2x | | 99.60=9.1a+72.3 | | 36=9(r-2) | | 70-3x=130-43x | | 35+42=12+x | | 9x+9=8x+4 | | 5x+7(7+3x)=4(9-8)+7 | | X+19=7+20 | | 99=98s+1 | | 8a^2+10ab^2+4ab+5b^3=0 | | 81-2x=92-3x | | 28=2w+24 | | f(0)=2x^3-5 | | 1.5sin(x)=sin(3x) | | 5x-17=12x-4 | | 2y^2+8y+2=0 | | 2(x+7)-6=x+15 | | (2x^3y^2)= | | (1-4y)(5-y)= | | 14s-10s=12 | | 2x+x+15=4x+10 | | 2c-7-8c=17 | | 4x+5=-37-10x# | | Y=17x+22 | | 10x+10x=20 |